Vaccine profile of 4CMenB: a four-component Neisseria meningitidis serogroup B vaccine - Esposito, Susanna; Principi, Nicola (Expert review of vaccines, 2014)
Invasive meningococcal disease is a severe clinical condition which most commonly presents as sepsis or meningitis and can cause death or major long-term sequelae. Neisseria meningitidis serogroup B (MenB) is one of the major causes of invasive meningococcal disease. The availability of the complete genome sequence of a MenB strain led to the development of a four-component vaccine specific for this pathogen (4CMenB), which has been tested in animals and humans. 4CMenB is shown to be immunogenic in pediatric subjects and is effective in vitro for most of the different MenB strains. However, several problems must still be adequately solved before the vaccine can be universally recommended. Further studies are needed to evaluate the vaccine's coverage over time, duration of protection, the immunogenicity of a simplified administration scheme, and the real incidence of severe rare adverse events. In addition, the effect of 4CMenB on MenB carriers and its cost-effectiveness ratio are needed to more completely describe the characteristics of this vaccine.